Nursing work in fall prevention perspective of elderly / Trabalho de enfermagem na perspectiva de prevenção de quedas de idosos - Bezerra, André Felipe Cavalcanti (2020)
This research addresses how nurses can act to prevent the fall of the elderly. The study is justified by the fact that the population over 60 years to be the most vulnerable to suffer falls and this realiade has increased over the past two decades in Brazil, and the elderly hospitalization increase due to this type of accident. This is a field research, quantitative and explanatory held at the Regional Hospital of the Wasteland Dr. Waldemiro Ferreira in Caruaru, Pernambuco. They interviewed ten nurses. The results indicate that nurses work in perspective to guide the elderly and their families to avoid falling, as they recognize the importance of nursing in prevention work; consider the Systematization of Nursing Assistance (SAE) as a facilitating tool of nursing,